2019
DOI: 10.1038/s41598-019-52488-9
|View full text |Cite
|
Sign up to set email alerts
|

Age and hippocampal volume predict distinct parts of default mode network activity

Abstract: Group comparison studies have established that activity in the posterior part of the default-mode network (DMN) is down-regulated by both normal ageing and Alzheimer’s disease (AD). In this study linear regression models were used to disentangle distinctive DMN activity patterns that are more profoundly associated with either normal ageing or a structural marker of neurodegeneration. 312 datasets inclusive of healthy adults and patients were analysed. Days of life at scan (DOL) and hippocampal volume were used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 55 publications
1
11
0
Order By: Relevance
“…These findings provide mechanistic insight into how exercise activates otherwise quiescent neurogenesis and alters hippocampal structure and function as well as how immature neurons play a central role in these changes. Considering that MRI studies in humans have demonstrated correlations between hippocampal volume and/or connectivity and cognitive ability ( De Marco et al., 2019 ; Lisofsky et al., 2015 ; Szymkowicz et al., 2016 ; Vecchio et al., 2017 ), we believe that our study offers a rational explanation for what may be occurring in the human brain following exercise and provides components that can be examined, especially in a longitudinal manner, to serve as useful indicators to optimize exercise in older adults to enhance cognitive function.…”
Section: Discussionmentioning
confidence: 82%
“…These findings provide mechanistic insight into how exercise activates otherwise quiescent neurogenesis and alters hippocampal structure and function as well as how immature neurons play a central role in these changes. Considering that MRI studies in humans have demonstrated correlations between hippocampal volume and/or connectivity and cognitive ability ( De Marco et al., 2019 ; Lisofsky et al., 2015 ; Szymkowicz et al., 2016 ; Vecchio et al., 2017 ), we believe that our study offers a rational explanation for what may be occurring in the human brain following exercise and provides components that can be examined, especially in a longitudinal manner, to serve as useful indicators to optimize exercise in older adults to enhance cognitive function.…”
Section: Discussionmentioning
confidence: 82%
“…The role of the anterior portion of the inferior parietal lobule was the common denominator of all three SRO-related trends ( Figure 2D ). This territory is part of the right temporoparietal junction, a region that has been widely studied in relation to perspective taking in social cognition ( Martin et al, 2020 ; Valera-Bermejo et al, 2021 ) and episodic memory processing ( De Marco et al, 2019 ). This region, however, serves a second major function, that is attentional reorienting ( Corbetta et al, 2008 ; Mitchell, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…DMN network strength is tightly associated with deposition of amyloid peptides in cognitively normal adults (Sheline et al, 2010;Sperling et al, 2009) as well as across the clinical spectrum of AD (Pasquini et al, 2017). A number of studies have investigated the link between selective anatomical/volumetric properties of the brain and DMN expression (De Marco et al, 2019;Frau-Pascual et al, 2019;Neufang et al, 2011;Saenger et al, 2012). No investigation, however, has yet focused on the intra-regional and interregional correspondence between volume and network expression of major DMN hubs.…”
Section: Introductionmentioning
confidence: 99%